2015
DOI: 10.1155/2015/469376
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health in a Sample of Pregnant Women from Northern Appalachia (2011–2015)

Abstract: Background. Chronic poor oral health has a high prevalence in Appalachia, a large region in the eastern USA. The Center for Oral Health Research in Appalachia (COHRA) has been enrolling pregnant women and their babies since 2011 in the COHRA2 study of genetic, microbial, and environmental factors involved in oral health in Northern Appalachia. Methods. The COHRA2 protocol is presented in detail, including inclusion criteria (healthy, adult, pregnant, US Caucasian, English speaking, and nonimmunocompromised wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 19 publications
0
48
0
Order By: Relevance
“…A caries assessment was conducted to yield an index of decayed, missing, and filled teeth (DMFT), including white spots. Examiners were trained and calibrated on all indices; reliability data can be found in Neiswanger et al (2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A caries assessment was conducted to yield an index of decayed, missing, and filled teeth (DMFT), including white spots. Examiners were trained and calibrated on all indices; reliability data can be found in Neiswanger et al (2015).…”
Section: Methodsmentioning
confidence: 99%
“…Information about training of examiners and inter-reliability can be found in Neiswanger et al (2015). Thereafter, participants were contacted by telephone for a structured interview by trained staff.…”
Section: Methodsmentioning
confidence: 99%
“…Interrater reliability scores (Cohen's kappa) for sound, decayed, and filled groups surface codes ranged from 82.1 to 92.5. Specific protocol for the clinical examination and calibration is described elsewhere [19]. Gingivitis was classified based on a soft tissue examination into localized, generalized, or hyperplasia.…”
Section: Data Collectionmentioning
confidence: 99%
“… 10 The first study, COHRA 1, conducted from 2000 to 2010 found high levels of dental caries in children: 5% in 2-year-olds, 21% in 3-year-olds, 35% in 4-year-olds, and 51% in 5-year-olds. 11 Another study, COHRA 2, is ongoing and involves the assessment of pregnant mothers and their babies. 11 …”
mentioning
confidence: 99%